Role of Kleda Dushya in Prameha (Diabetes Mellitus)-A Critical Review - Sharma, Parveen; Sumit; Sahu, Ajay Kumar; Bakuni, Harish; Padhar, Bharat Kumar; Rawat, Sunita (International Research Journal of Ayurveda & Yoga, 2022)
According to the World Health Organization, diabetes mellitus will be the seventh largest cause of death by 2030. According to studies undertaken by the Indian Council of Medical Research, India currently has 62.4 million persons with diabetes. Diabetes patients experience several consequences throughout time. As a result, they are vulnerable to a wide range of infections. Modern medical research is attempting to solve the problem, but it has its own limitations. According to modern medicine, the treatment’s goal is to achieve a protracted remission rather than a complete cure. According to Acharya Charaka, the vitiation of three Doshas creates 20 different varieties of Prameha as well as a slew of other ailments. Nidan, Dosha, and Dushya are three components that, when united in a strong state, cause Prameha to develop right away. The patient in Madhumeha passes a big amount of urine that looks like Madhu (honey) and tastes like Kashaya (astringent) and Madhur (sweet). In place of Madhumeha, Acharya Sushruta has told Kshaudrameha. An individual suffering from prameha’s like is also increased by hereditary propensity. The unnecessary Abaddha meda (loose lipid), Mamsa (muscle proteins), Kleda (body fluids), Shukra (reproductive tissues), Shonit (blood), vasa (muscle fats), Majja (bone marrow), Rasa (body liquid with plasma), Oja (immunity and immune system of body) are significant components engaged with the pathogenesis of prameha. The present review highlights the role of Kleda dushya in the pathogenesis of Diabetes Mellitus.